Dynamic Article: Full-Thickness Excision for Benign Colon Polyps Using Combined Endoscopic Laparoscopic Surgery. Issue 1 (January 2016) - Lin, Anthony Y.; O'Mahoney, Paul R. A.; Milsom, Jeffrey W.; Lee, Sang W.
Abstract : BACKGROUND: Benign colon polyps are commonly encountered but may not always be amenable to endoscopic excision because of their size, shape, location, or scarring from previous attempts. The addition of laparoscopy allows a greater degree of bowel manipulation, but the current technique is still limited when encountering a polyp with inadequate lifting attributed to polyp morphology or scarring. We describe an extension to the existing combined endoscopic laparoscopic surgery technique using a full-thickness approach to increase polyp maneuverability and local excision of difficult but benign polyps. OBJECTIVE: The purpose of this study was to report the technical details and preliminary results of a new approach for full-thickness excision of difficult colon polyps, combined endoscopic laparoscopic surgery full-thickness excision. DESIGN: This study is a retrospective review of our experience from December 2013 to May 2015. SETTINGS: The study was conducted at a single academic institution. PATIENTS: All of the patients had previous incomplete colonoscopic polypectomy performed at other institutions. Patients were selected for our technique if the polyp had a benign appearance but was unable to be resected by traditional endoscopic or combined endoscopic laparoscopic surgery methods because of polyp morphology or scarring from previous biopsies. MAIN OUTCOME MEASURES: The safety and feasibility of this procedure were measured. RESULTS: Three patients underwent combined endoscopic laparoscopic surgery–full-thickness excision for difficult colon polyps. There were no intraoperative or postoperative complications. The length of stay was 1 day for all of the patients. All 3 of the patients had benign final pathology. LIMITATIONS: This study was limited by the small number of patients in a single institution. CONCLUSIONS: Full-thickness excision for benign colon polyps using combined endoscopic laparoscopic surgery is safe and feasible. Using this technique, difficult polyps not amenable to traditional endoscopic approaches can be removed and colectomy may be avoided. Abstract : Supplemental Digital Content is available in the text.